Valuation Effects of Foreign Company Listings on U.S. Exchanges - Sundaram, Anant K.; Logue, Dennis E. (Journal of International Business Studies, 1996)
This study examines post-listing equity price performance of foreign firms which cross-listed sponsored American Depository Receipts (ADRs) on the New York and the American Stock Exchanges during the period 1982-1992. We use three valuation metrics – price-to-book, price-to-cash-earnings, and price-to-earnings – which are adjusted for the home country and world industry indices to which the listing firm's stock belongs. We find positive valuation effects associated with cross-listing for both country-benchmarked and industry-benchmarked price ratios. Variables that proxy for home country characteristics such as governance styles, disclosure quality, market liquidity, and so forth are unable to explain the cross-sectional variation in the data. Our results thus suggest that cross-listing in the U.S. enhances valuations for listing firms by simply reducing the overall effect of segmentation among different national securities markets.